STRATEGI POLITIK ARISTOKRAT DI PEMILU (Studi komparatif Tentang Kemenangan Sultan Ternate dan kekalahan Sultan Tidore dan Sultan Jailolo di Pemilihan Umum DPD RI Tahun 2009 di Provinsi Maluku Utara) - , SUBKHAN TOMAITO, Drs. Cornelis Lay, MA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study on "Political Strategies Aristocrat In Elections", which focuses on the victory of the Sultan of Ternate, the defeat of Sultan and Sultan Tidore Jailolo DPD in the General Election of 2009 in the province of North Maluku. In other words, how the strategy of the aristocrat who fought in the electoral arena (DPD elections) in 2009. In this study uses a comparative study by using a qualitative approach and refers to the primar and sakunder. While the data obtained through field observations, as well as in-depth interviews (depth interview) to the berkompotensi informain related to the problem under study, and documentation. The results showed the electoral victory of the Sultan of Ternate in 2009, among other DPD because the Sultan of Ternate (Mudaffar Sjah) was able to capitalize on the modalities of a strategy in the arena of electoral politics. Sultan of Ternate in the community also has the charisma, the Sultan of Ternate is supported by the community structure of ancestral lands and customary institutions, In addition it is also the Sultan of Ternate (Mudaffar Sjah) are intellectually and politically has been recognized by the public in North Maluku have experienced as a politician and member of the Assembly of new Order until now. While the defeat of Sultan and Sultan Jailolo Tidore in the arena of electoral DPD 2009 because both the sultan was not able to capitalization modality as a political strategy. And lack of socialization themselves against the weakness of public and political communication with the elite and society and not supported by traditional structures in each region. Political communication is not awakened by the political elite and when both the empire was elected in both national and local legislatures can not do much for the sake of the region. Conclusions obtained in this study is that the role of ownership modalities and strategies in electoral politics as a whole that can not be separated or interconnected with each other. This means that, in an electoral competition, Aristocrat should be able to capitalize on the modalities in the arena as a political strategy to win the electoral.